The architecture of the Luwu Palace as a reflection of Bugis history and culture - Dwiasta, Andi Yusdy; Jayadi, Karta; Abidah, Andi (2025)
The Luwu Langkanae Palace is a form of traditional Bugis architecture that reflects the cosmology, social structure, and cultural values of the Luwu community. This research examines the architectural elements of the Luwu Langkanae Palace with a focus on its symbolism. The spatial arrangement of the palace, which includes the division between the main space (ale bola), the kolong (lower space), and additional rooms, illustrates the social organization and ritual functions of the community. The towering roof and symbolic ornaments emphasize the connection between the physical and spiritual aspects of the building's design, reflecting the cosmological views of the Luwu people. The history of the palace as a center of power and culture since the 12th century, along with efforts for maintenance and renovation, highlights the significance of the palace in the context of cultural heritage and local identity. In conclusion, the Luwu Langkanae Palace is a manifestation of deep cosmological and social values, serving as a symbol of cultural heritage and a center for the preservation of Bugis history.